The girl on the train - Hawkins, Paula; Corbett, Clare; Brealey, Louise; Fisher, India, 1974- (New York, NY : Penguin Audio, 2015)
Obsessively watching a breakfasting couple every day to escape the pain of her losses, Rachel witnesses a shocking event that inextricably entangles her in the lives of strangers.
Title from container.
Read by Clare Corbett, Louise Brealey, and India Fisher.
Keywords: Railroad travel -- Fiction; Commuters -- Fiction; Strangers -- Fiction; London (England) -- Fiction; Suspense fiction; Audiobooks; Psychological fiction